Pengaruh Brand Experience Terhadap Customer Loyalty yang Dimediasi Oleh E-Commerce Trust dan E-Commerce Satisfaction pada Platform Shopee - Brilianty Sekar Amalia; Uhud Darmawan Natsir; Ilma Wulansari Hasdiansa; Chalid Imran Musa; Nurul Fadilah Aswar (Jurnal Publikasi Manajemen Informatika, 2024)
In 3 consecutive years shopee has been nominated as one of the top e-commerce site by the Indonesian people even though there are many selection of e-commerce available in the country shopee's gross merchandise value continues to increase, this study purposed is to examine how is the Brand Experience on Shopee Customer Loyalty mediated by E-Commerce Trust and E-Commerce Satisfaction among students majoring in management at Makassar state university. In this study, the variables that is going to be used in this study is Brand Experience as the dependent variable (X), Customer Loyalty as the independent variable (Y), and E-Commerce Trust and E-Commerce Satisfaction as mediating variables (Z). Respondents that is participating in this study will be the active students of Makassar State University. Data collection is carried out online by utilizing google form. The data analysis technique that will be utilized in this research is Structural Equation Modeling-Partial Least Square (SEM-PLS) for this study researcher decided to use SmartPLS 4. The results of this study is: Brand Experience has a positive and significant relationship with Customer Loyalty through E-Commerce Trust Shopee among Management Students of Makassar State University. [Brand Experience, Customer Loyalty, E-Commerce Trust dan E-Commerce Satisfaction]